Fusion of multi-focus images with registration inaccuracies. Issue 3 (March 2017) - Ahmad, Attiq; Ahmad, Sahar; Khurshid, Hasnat; Riaz, M.; Ghafoor, Abdul; Zaidi, Tahir
Abstract Image fusion combines complementary information for several input images. To obtain useful information from two misaligned images, registration is required. A hybrid textural registration-based multi-focus image fusion scheme is proposed. The Gabor filtering with specific frequency and orientation is used to extract different texture features from the image. The resulting Gabor-filtered images are then aligned using existing affine transformation. The proposed registration scheme yields superior performance as compared to affine registration, as Gabor transform extracts all the features. The fusion is performed using undecimated dual-tree complex wavelet transform. The quantitative and qualitative analysis of the proposed scheme outperforms existing image fusion schemes.